Influence of Simulated and Actual Community Vaccination Clinics on Student Empowerment and Self‐Efficacy for Public Health Nursing Competencies. Issue 3 (21st August 2014) - Babenko‐Mould, Yolanda; Ferguson, Karen; Riddell, Thelma; Hancock, Michele; Atthill, Stephanie
Abstract Objectives To examine students' structural empowerment during simulated learning and actual nursing practice, and assess students' self‐efficacy for public health nursing competencies (PHNC) after involvement in a mass influenza vaccination clinic as a community practice experience. Design A nonexperimental survey design was used with a sample of year three baccalaureate nursing students. Methods Students completed a demographic form after the simulated clinic experience, they were assessed for perceptions of empowerment after being involved in the simulated and actual clinic settings, and self‐efficacy was assessed after the actual clinic experience. Results Students perceived themselves as structurally empowered after completing the simulated and actual community vaccination clinics. Students reported a high level of self‐efficacy for PHNC after their actual community vaccination clinic involvement. There was a significant correlation between empowerment and self‐efficacy, which suggests that when students have access to empowering structures, they feel more confident to enact PHNC that align with practice in the clinics. Conclusion This study suggests that nursing students acquired the necessary knowledge and skills for safe vaccination administration through the combination of simulated practice and participating in an actual public health vaccination clinic.